United Arab Emirates (UAE) leadership in controlling COVID-19: practical policy steps and outcomes - Taghreed M. Abu Sarhan; Shamma J. AlFalasi (Journal of Global Health Economics and Policy)
# Background With the global outbreak of coronavirus in 2019 (COVID-19), governments across the globe faced the challenge of outlining policy capacity to contain the spread of infection and overcome human tragedy. To overcome this global public health emergency, the government of the United Arab Emirates (UAE) used a rigorous approach to mitigate the consequences of this non-communicable pandemic through effective approaches. Therefore, the study aimed to explore the role of the leadership of the United Arab Emirates (UAE) in controlling COVID-19. It figured out the practical policy steps and outcomes.